A Study of Developing Gastronomy Tourism in the Areas of Different Contexts: Case Study of Nakhonpathom Province - Sakulrattanakulchai, Satida; Sanguansintukul, Kannika (Journal of Architectural/Planning Research and Studies (JARS), 2020)
Based on community resources conducive to gastronomy tourism, this research selected Nakhonpathom Province as a case study. The objectives of the research were to 1) analyze the potential of Nakhonpathom Province and the study areas toward gastronomy tourism, 2) analyze the problems and needs of the stakeholders in the areas, and 3) propose guidelines for gastronomy tourism development of Nakhonpathom Province. Research was conducted by selecting the study areas from each district. Data was collected from documenting, surveying, and mapping methods, including interviewing 120 people. The variables framework based on the concept of area-based development. The results were found that Nakhonpathom Province and the seven study areas, Phrapathom-Chedi Night Market (Mueang district), Thana Market (Nakhonchaisi district), Donwai Market (Samphran district), Lamphaya Floating Market (Banglen district), Ban-Saladin Community Mahasawat Canal (Phutthamonthon district), Laos-Khrang Community Ban-Thungphakkut (Dontum district) and Thai-Song-Dam Community Ban-Nongthiam (Kamphaengsaen district), have potential for gastronomy tourism. The strengths of all sites are physical resources, activities, knowledge and skills, cultures and identities, and images. The gastronomy tourism development guidelines are divided into two levels. The first level, for the study areas. is proposed as physical and policy guidelines. The second level, for the province, is presented as four tourism types which are the gastronomy tourism on riverside areas, the cultural tourism and local food, the gastronomy tourism an agricultural community, and the gastronomy tourism at a night market. Propose guidelines for design, improvement, and development of the physical environment strengthening from the potential of each type of tourism.